Development of research skills and formative research in higher education. - Mazuelos Chávez, Eliana; Aguayo Polar, Víctor Hugo (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The university has been using the concept of formative research for the fulfillment of one of its functions within the framework of the law. Since then we have conducted research on the development of research skills in the university classroom, we present activities developed by professors, which bring us closer to the use of tools that allow the development of research skills from the training process. Material and methods: it was based on an exploratory descriptive descriptive research, as well as on the documentary analysis carried out at different times. First: institutional diagnosis on formative research, second: design of the conceptual model and third: construction of exploratory scenarios.